Investigating factors influencing the preference for going out - Sumiko Ishibashi; Mamoru Taniguchi (Transportation Research Interdisciplinary Perspectives)
The rise of digitalization has reduced the need for daily out-of-home activities such as commuting to the office, shopping at stores, and meeting in person. However, a complete shift to online activities can be harmful to individuals and society. In a highly digitalized society where “going out” is optional, understanding people’s preferences for going out could be crucial to encourage them to voluntarily go out and support favorable out-of-home experiences. This study investigates individuals’ perceived values that affect the levels of preference for going out through an original web-based survey conducted in Japan (N = 885). The findings reveal that the perceived burdens of preparation and social interactions have a negative effect, whereas vague but positive expectations for an out-of-home experience and a positive perception of the place of activity and travel have positive impacts. Environmental and personal factors that may lower the perceived burden and raise positive expectations for going out include (1) better accessibility to urban functions; (2) a personal sense of openness, extraversion, and low conscientiousness; and (3) interhuman relationship-building with family and neighborhood members. Surprisingly, travel costs and time did not negatively affect the preference for going out, but these costs remain burdensome to younger people, low-income households, and those who like going out. Our findings support the growing awareness of the need for improving accessibility and better community building.